Upfront and repeated stereotactic radiosurgery in patients with brain metastases from NSCLC - Krämer, Anna Sabrina; Adeberg, Sebastian; Kronsteiner, Dorothea; König, Laila; Schunn, Fabian; Bozorgmehr, Farastuk; Christopoulos, Petros; Eichkorn, Tanja; Schiele, Annabella; Hahnemann, Laura; Rieken, Stefan; Debus, Jürgen; et al. (Clinical lung cancer, 2023)
Introduction - Approximately 40% of non-small-cell lung cancer (NSCLC) patients develop brain metastases (BM). Stereotactic radiosurgery (SRS) instead of whole-brain radiotherapy (WBRT) is increasingly administered as an upfront treatment to patients with a limited number of BM. We present outcomes and validation of prognostic scores for these patients treated with upfront SRS. - Methods - We retrospectively analyzed 199 patients with a total of 268 SRS courses for 539 brain metastases. Median patient age was 63 years. For larger BM, dose reduction to 18 Gy or hypofractionated SRS in 6 fractions was applied. We analyzed the BMV-, the RPA-, the GPA- and the lung-mol GPA score. Cox proportional hazards models with univariate and multivariate analyses were fitted for overall survival (OS) and intracranial progression-free survival (icPFS). - Results - Sixty-four patients died, 7 of them of neurological causes. Thirty eight patients (19,3%) required a salvage WBRT. Median OS was 38, 8 months (IQR: 6-NA). In univariate analysis as well as multivariate analysis, the Karnofsky performance scale index (KPI) ≥90% (P = 0, 012 and P = 0, 041) remained as independent prognostic factor for longer OS. All 4 prognostic scoring indices could be validated for OS assessment (BMV P = 0, 007; RPA P = 0, 026; GPA P = 0, 003; lung-mol GPA P = 0, 05). - Conclusion - In this large cohort of NSCLC patients with BM treated with upfront and repeated SRS, OS was markedly favourable, in comparison to literature. Upfront SRS is an effective treatment approach in those patients and can decidedly reduce the impact of BM on overall prognosis. Furthermore, the analysed scores are useful prognostic tools for OS prediction.